2019
DOI: 10.1002/lsm.23107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photobiomodulation Therapy on the Increase of Viability and Proliferation of Human Mesenchymal Stem Cells

Abstract: Background and Objectives We have investigated how low intensity laser irradiation emitted by a multiwave‐locked system (MLS M1) affects the viability and proliferation of human bone marrow mesenchymal stem cells (MSCs) depending on the parameters of the irradiation. Study Design/Materials and Methods Cells isolated surgically from the femoral bone during surgery were identified by flow cytometry and cell differentiation assays. For irradiation, two wavelengths (808 and 905 nm) with the following parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…BMSCs are MSCs readily isolated from the bone marrow that can support angiogenesis, enhance secretion of nerve growth factors (NGFs), restore nerve function after ischemic stroke, and treat non-healing fractures. 34 Many studies point to the potential BMSCs have for wound healing, fat production, and bone formation. However, regarding these applications of PBM on BMSCs, wavelengths in the near-infrared regions (808 and 890 nm) produced more significant and remarkable results.…”
Section: Bone Marrow-derived Stem Cells (Bmscs)mentioning
confidence: 99%
“…BMSCs are MSCs readily isolated from the bone marrow that can support angiogenesis, enhance secretion of nerve growth factors (NGFs), restore nerve function after ischemic stroke, and treat non-healing fractures. 34 Many studies point to the potential BMSCs have for wound healing, fat production, and bone formation. However, regarding these applications of PBM on BMSCs, wavelengths in the near-infrared regions (808 and 890 nm) produced more significant and remarkable results.…”
Section: Bone Marrow-derived Stem Cells (Bmscs)mentioning
confidence: 99%
“…65 A recent study demonstrated that PBMT can act on migration, differentiation and production of extracellular matrix molecules by progenitor cells. 66 Based on the results of in vitro studies, significant evidence of an upregulation of the regenerative capacity of MSCs has been accumulated. The combined use of BMA plus PBMT seems to be a good strategy in the clinical scenario.…”
Section: Enhancement Of the Bma Clotmentioning
confidence: 99%
“…The treatment method includes low-level laser therapy and laser acupuncture [ 12 , 13 ]. Studies indicate that laser acupuncture for Bell's palsy can reduce pain and have anti-inflammatory effects, though the exact mechanism remains unclear [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%